2016
DOI: 10.1080/13102818.2016.1258330
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and the presence of anti-sperm antibodies

Abstract: The aim of this study was to investigate the possible association between serum anti-Helicobacter pylori antibodies and anti-sperm antibodies (ASA) in patients with gastroduodenal diseases caused by H. pylori, infertile patients positive for ASA and healthy fertile blood donors as controls. Serum ASA were studied by sperm agglutination tests, sperm immobilization test and ELISA against sperm antigens (ELISAsp). Serum IgG anti-H. pylori antibodies were detected by ELISA (ELISAHp). The tests revealed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…This may be attributed to the fact that most of these previous studies were carried out in developed countries with higher socioeconomic standard of residents and with better sanitary conditions which limit the spread of faecal oral infections in general. H. pylori prevalence rate among cases of idiopathic infertility in the present work was 79.7%; which is relatively high in comparison to previous reports as those of Collodel et al, (2010) (45%), (12) Figura et al, (2002) (7) and Dimitrova-Dikanarova et al, (2017), (8) ;(66.6%) each. A high prevalence rate of 79.4 % was recorded for H. pylori among cases with secondary infertility in the current work vs. 69.7% among those with primary infertility.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…This may be attributed to the fact that most of these previous studies were carried out in developed countries with higher socioeconomic standard of residents and with better sanitary conditions which limit the spread of faecal oral infections in general. H. pylori prevalence rate among cases of idiopathic infertility in the present work was 79.7%; which is relatively high in comparison to previous reports as those of Collodel et al, (2010) (45%), (12) Figura et al, (2002) (7) and Dimitrova-Dikanarova et al, (2017), (8) ;(66.6%) each. A high prevalence rate of 79.4 % was recorded for H. pylori among cases with secondary infertility in the current work vs. 69.7% among those with primary infertility.…”
Section: Discussioncontrasting
confidence: 56%
“…In previous surveys, it was reported that H. pylori was more prevalent among the infertile population and played a negative influence on sperm motility, viability and morphology; either through increasing the systemic and the semen levels of inflammatory cytokines or by promoting autoimmunity. (8) In the current work, H. pylori infection didn't significantly affect the quality of semen profile in seropositive cases in comparison to seronegative ones. Meanwhile CagA seropositivity significantly affected the seminal profile.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations